A percepção da paisagem turística em São Jerônimo da Serra e Nova Santa Bárbara : uma reflexão a partir da geografia cultural - Luz, Coaracy Eleutério da (2015)
The research covers as study area the municipalities of Nova Santa Bárbara and São Jerônimo da Serra, located in the middle region of Norte Pioneiro Paranaense, whose both socioeconomic situation is characterized by low dynamism and expressiveness over the decades of this century. On the other hand, the focus given to the studied area derives from its huge diversity of natural and cultural components of the landscape, planned as rich tourist potential to be developed. Judging such a question as worthy of an analytical exercise, initially the landscape category appears during the evolution of geographical science, then the appropriate relationship between landscape and tourism, with emphasis on the tensioned tourist modalities. Through this theoretical framework we proceed the geographical interpretation and identification of the tourist potential of the municipalities analyzed. It is concluded that their landscapes investigated show remarkable components of natural and cultural order, representing such potential for the tourism development aspirated.